MODERN METHODS OF TREATMENT OF BREAST CANCER - Mirakhmedova Sohiba Soibnazar kizi (Web of Journals Publishing, 2025)
The features of morbidity and the significance of constitutional factors – age, menstrual status, height, weight, body mass index- were studied.
Keywords: Edematous breast cancer; body mass index, age, menstrual status nodular forms of breast cancer.